2014
DOI: 10.1016/j.urology.2014.02.073
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obstructive Sleep Apnea Syndrome on Nocturnal Urine Production in Older Men With Nocturia

Abstract: Our results indicated that older men with nocturnal polyuria and OSAS did not compensate their fluid imbalance presented with decreased secretion of ADH but increased BNP level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
0
14
0
5
Order By: Relevance
“…16 However, also sleep disorders such as OSA and periodic limb movements during sleep (PLMS) are associated with NP, nocturnal enuresis (NE), and nocturia. [17][18][19][20]…”
Section: Better Understanding Of Sleep Better Understanding Of Noctumentioning
confidence: 99%
“…16 However, also sleep disorders such as OSA and periodic limb movements during sleep (PLMS) are associated with NP, nocturnal enuresis (NE), and nocturia. [17][18][19][20]…”
Section: Better Understanding Of Sleep Better Understanding Of Noctumentioning
confidence: 99%
“…3 A recent study has looked at brain natriuretic peptide (BNP) and antidiuretic hormone (ADH) in patients with and without OSA. 4 The results showed that patients with OSA had a significantly higher BNP, but no difference in ADH. Surprisingly, the non-OSA group had a higher nocturia rate and 24-hour frequency than the OSA group.…”
Section: Osa and Increased Urine Productionmentioning
confidence: 91%
“…Obstructive sleep apnoea is a common cause of nocturia through the effect of increased brain natriuretic peptide . In this case the patient's presenting symptom may be nocturia and only by directed questioning, examination, and review of a bladder diary will the possibility of sleep apnoea be identified.…”
Section: Diagnosis and Clinical Assessmentmentioning
confidence: 99%